MIP-graphene-modified glassy carbon electrode for the determination of trimethoprim - Silva, Hélder (2014)
A novel sensitive electrochemical sensor was developed by electropolymerization of pyrrole(PY)and molecularly imprinted polymer (MIP)which was synthesized onto a glassy carbon electrode (GCE) in aqueous solution using cyclic voltammetry in the presence of Trimethoprim (TMP) as template molecules. Furthermore,a previous electrode modification was performed by deposition of a suspension of graphene on the electrode's surface. The performance of the imprinted and non-imprinted (NIP) films was evaluated by impedance spectroscopy (EIS) and cyclic voltammetry (CV) of a ferric solution. The molecularly imprinted film exhibited a high selectivity and sensitivity toward TMP. The sensor presented a linear range, between peak current intensity and logarithm of TMP concentration between 1.0x10-6 and 1.0x10-4 M. The results were accurate (with recoveries higher than 94%), precise (with standard deviations less than 5%) and the detection limit was 1.3x10-7 M. The new sensor is selective, simple to construct and easy to operate. The MIP sensor was successfully applied to quantify TMP in urinesamples.